2020
DOI: 10.1111/ases.12883
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative pneumonia after laparoscopic gastrectomy in patients aged 75 years and over with gastric cancer

Abstract: Introduction The proportion of patients aged 75 years and over who undergo minimally invasive surgery for gastric cancer is increasing. However, the safety and feasibility of laparoscopic gastrectomy (LG) in this age group is controversial. This study aimed to evaluate whether LG is safe and effective in patients aged 75 years and over. Methods The study included 728 patients with early and advanced gastric cancer who underwent curative LG between 2009 and 2017; 166 of these patients (22.8%) were aged 75 or ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Postoperative pneumonia was more common in low CXI patients. Reported risk factors for postoperative pneumonia after surgery for GC include advanced age, poor nutritional status, total gastrectomy, time to first meal after surgery, extended operation times, D2 lymph node dissection, advanced tumor stage, and predicted vital capacity [34][35][36][37]. It is difficult to prevent pneumonia via surgical techniques because the extent of gastrectomy and lymph node dissection is essentially predetermined by tumor location and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pneumonia was more common in low CXI patients. Reported risk factors for postoperative pneumonia after surgery for GC include advanced age, poor nutritional status, total gastrectomy, time to first meal after surgery, extended operation times, D2 lymph node dissection, advanced tumor stage, and predicted vital capacity [34][35][36][37]. It is difficult to prevent pneumonia via surgical techniques because the extent of gastrectomy and lymph node dissection is essentially predetermined by tumor location and progression.…”
Section: Discussionmentioning
confidence: 99%
“…As well as the extent of gastrectomy, the extent of lymphadenectomy is also recommended to be limited in patients aged ≥ 80 years [ 19 ]. A recent paper showed that D2 lymphadenectomy was an independent risk factor for postoperative pneumonia in patients aged ≥ 75 years [ 20 ]. In our study, ≥ D2 lymphadenectomy provided fair prognoses, and D1+ lymphadenectomy was also acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pneumonia was more common in frail patients in our study. Risk factors for postoperative pneumonia after surgery for GC have been reported and include advanced age, poor nutritional status, total gastrectomy, time to rst meal after surgery, extended operation time, D2 lymph node dissection, advanced tumor stage, and predictive vital capacity (VC) [24][25][26][27] . Several large trials have shown that the incidence of postoperative pneumonia was not signi cantly different between LG and OG 21,22,28 .…”
Section: Discussionmentioning
confidence: 99%